PERAN KOREOGRAFER PEREMPUAN DALAM PERKEMBANGAN TARI - Sri Rochana Widyastutieningrum (Pascasarjana Institut Seni Indonesia Surakarta, 2012)
This article is the result of anobservation of the role of female chorographers in the development of dance inIndonesia. The roleof female choreographers in the development of dance can be divided into four aspects, namely choreographers as creators ofdance, choreographers as dancers, choreographers as preservers of traditional dance, and choreographers as supporters of thedevelopment of dance. In carrying out the role of a choreographer as a creator of dance, a high level of creativity is required, andthis is influenced by the choreographer’s cultural background, environment, talent, education, and love of dance. The role offemale choreographers in creating dance is evident in the fact that they have created various newforms of dance, in terms oftheir numerous ideas, forms, types, and styles, so that dance performances have becomemore attractive andmore animated.Thepresence of these newdances has also enhanced the aesthetical values of existing dances, enriched the spiritual experience ofthe dancers and the audience, and added to thewealth of variety in theworld of dance. Female choreographers have the scopeand freedomto express real-lifewomen’s issues related to the complex problems of life, based on awoman’s point of view. Incarrying out this role, a choreographer also functions as a dancer, a preserver of traditional dance, and a supporter of thedevelopment of dance.Keywords: role, female choreographer, dance creation, tradition.